2017
DOI: 10.16965/ijpr.2017.117
|View full text |Cite
|
Sign up to set email alerts
|

Role of Swiss Ball Exercises in Reducing Pain, Disability and Improving Muscle Endurance in Patients With Mechanical Low Back Ache

Abstract: Introduction: Low back pain is a very common health problem associated with considerable disability and costs to society. Low back pain is becoming increasingly common. Approximately 70-90% of our population suffers from low back pain or has suffered from multiple episodes of low back pain. Pain aggravated by extension, sideflexion, rotation, standing, walking, sitting, and exercise in general, and relieved by changing in position. Many different therapeutic interventions are used in the management of low back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
2
Order By: Relevance
“…The result of the present study shows that subjects in Pilates group show a significant improvement in core muscle strength. Raghav et al, showed that with the six weeks protocol there was significant difference between post treatment values of VAS score, ODI score, DAET score and DEET score taken on 42 nd day (8). Bhem et al, showed that exercises performed on unstable (Swiss ball) surface stressed the musculature and activated the proprioception activity and gain the stability (9).…”
Section: Discussionmentioning
confidence: 99%
“…The result of the present study shows that subjects in Pilates group show a significant improvement in core muscle strength. Raghav et al, showed that with the six weeks protocol there was significant difference between post treatment values of VAS score, ODI score, DAET score and DEET score taken on 42 nd day (8). Bhem et al, showed that exercises performed on unstable (Swiss ball) surface stressed the musculature and activated the proprioception activity and gain the stability (9).…”
Section: Discussionmentioning
confidence: 99%
“…If there are impulses that are transmitted by large diameter fibers due to skin stimulation, touch, vibration, warm or cold sensation and soft touch then these impulses will inhibit impulses from small diameter fibers so that the sensations carried by small fibers will be reduced or not delivered to the brain by SG so that the body does not feel the sensation of pain 7 Swiss ball is an exercise technique using a ball, where the purpose of this exercise is to strengthen muscles, increase ligament flexibility so that lumbar stabilization is improved. Using swiss ball exercises where there is an isometric and isotonic muscle contraction resulting in a vasoconstriction effect on blood vessels where circulation will be smooth and O2 nutrition to the muscles improves 5 The research results 4 exercises is proven to increase endorphin levels four to five times in the blood, so the more the physical exercise the higher the endorphin levels so that it can reduce pain during menstruation.…”
Section: B Discussion 1) Differences In the Scale Of Menstrual Pain Before And After The Swiss Ball Exercise Technique On The Interventiomentioning
confidence: 99%
“…Pharmacological therapies that can be used are Non-Steroids Anti-Inflammatory Analgesics (NSAIDs), for example paracetamol, mefenamic acid, and metamizole, but there are negative effects when using drugs continuously 2 Non-pharmacological therapy that can be carried out to reduce menstrual pain is acupressure and stretching, endorphin massage 3 . However, there are other techniques called Swiss ball exercise which is one of the nonpharmacological management that is safe because it uses more physiological processes 4 . Research results from 5 says by doing an exercise the body will produce endorphins produced in the brain and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Di Indonesia, penelitian yang dilakukan oleh Community Oriented Program for Controle of Rheumatic Disease/COPORD:2009 menunjukkan prevalensi nyeri punggung bawah 18,2% pada laki-laki dan13,6% pada wanita (Rumiyati et al, 2019) Penelitian yang dilakukan kelompok studi nyeri PERDOSSI pada 14 rumah sakit pendidikan di Indonesia, pada bulan Mei 2002 menunjukkan jumlah penderita nyeri sebanyak 4.456 orang (25% dari total kunjungan), dimana 1.598 orang (35,86%) adalah penderita nyeri punggung bawah (Raghav & Singh, 2017) (Lubis, 2003).…”
Section: Pendahuluanunclassified